2010
DOI: 10.1128/ec.00166-10
|View full text |Cite
|
Sign up to set email alerts
|

The Antiretroviral Lectin Cyanovirin-N Targets Well-Known and Novel Targets on the Surface of Entamoeba histolytica Trophozoites

Abstract: Entamoeba histolytica, the protist that causes amebic dysentery and liver abscess, has a truncated Asn-linked glycan (N-glycan) precursor composed of seven sugars (Man 5 GlcNAc 2 ). Here, we show that glycoproteins with unmodified N-glycans are aggregated and capped on the surface of E. histolytica trophozoites by the antiretroviral lectin cyanovirin-N and then replenished from large intracellular pools. Cyanovirin-N cocaps the Gal/GalNAc adherence lectin, as well as glycoproteins containing O-phosphodiester-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…Two LC-MS/MS proteomic datasets were available for the trophozoite stage of E. histolytica comprising a total of 1825 proteins (as of November 30, 2011) [29], [30]. There was also available an EST database for E. histolytica trophozoite comprising a total of 1223 proteins (as of October 1, 2011; from a total of 20,812 public entries at http://www.ncbi.nlm.nih.gov/dbEST/dbEST_summary.html).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two LC-MS/MS proteomic datasets were available for the trophozoite stage of E. histolytica comprising a total of 1825 proteins (as of November 30, 2011) [29], [30]. There was also available an EST database for E. histolytica trophozoite comprising a total of 1223 proteins (as of October 1, 2011; from a total of 20,812 public entries at http://www.ncbi.nlm.nih.gov/dbEST/dbEST_summary.html).…”
Section: Resultsmentioning
confidence: 99%
“…Since the total number of proteins identified in the naturally-occurring cyst samples was small, we asked how unique these proteins are in comparison with the publicly available protein datasets in AmoebaDB ( http://amoebadb.org/amoeba/ ). Two LC-MS/MS proteomic datasets were available for the trophozoite stage of E. histolytica comprising a total of 1825 proteins (as of November 30, 2011) [29] , [30] . There was also available an EST database for E. histolytica trophozoite comprising a total of 1223 proteins (as of October 1, 2011; from a total of 20,812 public entries at http://www.ncbi.nlm.nih.gov/dbEST/dbEST_summary.html ).…”
Section: Resultsmentioning
confidence: 99%
“…However, we observed a large difference in the rate of occupancy of potential N-glycosylation sequons. Despite the 5:3 ratio of Thr (100) and Ser (61) in the second position relative to Asn, the number of occupied N-glycan sites overwhelmingly (9:1) favors Thr (35) over Ser (4), as shown in the WebLogo in Fig. 6 and the data in Table I (46).…”
Section: Heavily Glycosylated Proteins Include An Immunodominant Protmentioning
confidence: 92%
“…The binding of the anti-retroviral lectin cyanovirin-N to C. parvum strongly suggested that the parasite contains a high mannose N-glycan (23,24). Cyanovirin-N also binds to Entamoeba and Trichomonas, each of which builds its N-glycans from a precursor composed of Man 5 GlcNAc 2 (61)(62)(63). The N-glycan profile of C. parvum differs from those of the other parasites in the relative abundance of GlcMan 5 GlcNAc 2 and the absence of mannosidase products (Man 4 GlcNAc 2 and Man 3 GlcNAc 2 ) and/or hybrid and complex N-glycans, which contain LacNAc arms (Trichomonas) or galactose capped with Glc (Entamoeba) (63,64).…”
Section: Heavily Glycosylated Proteins Include An Immunodominant Protmentioning
confidence: 99%
“…Many N -glycans, however, remain unmodified by ER mannosidases and Golgi glycosyltransferases and so are recognized by lectins that bind to the single 1,3-linked mannose arm of Man 5 GlcNAc 2 (e.g. cyanovirin- N binding to Entamoeba , Trichomonas , Toxoplasma , and Cryptosporidium ) [29, 42, 43]. Similarly, wheat germ agglutinin or Griffonia simplicifolia lectin II binds to unmodified GlcNAc 2 of Giardia and Plasmodium [28, 29].…”
Section: The Present Diversity Of N-glycan Precursorsmentioning
confidence: 99%